Implementasi Nilai-Nilai Dakwah dalam Membina Masyarakat Pluralitas (Studi pada Kegiatan Dakwah Nahdlatul Ulama Kecamatan Jati Agung Lampung Selatan) - Nasor, M. (AL-ADYAN, 2017)
Da'wah activities in plurality communities not only have strong basic principles of faith but also can realize basic moral principles and social ethics. Their existence must get guidance so that the community has the character of loving kindness, opposing evil, and not knowing violence in accordance with Islamic teachings. In such conditions the basis of a strong faith will be able to create a life that is in harmony with everyday life such as a sense of social justice, security, mutual help, respect, and others. The values of da'wah mentioned above must be implemented in daily life in a plurality society by referring to the principles, namely: (1) Islamic civilization stands on the basis of monotheism, (2) civilizations that are human, transcendental, and have international insight, (3) always hold moral principles, (4) believe in the right knowledge, and (5) have religious tolerance. Universal values of da'wah regulate relationships based on aspects of mutual respect, non-coercion, principles of justice, humanity, togetherness, brotherhood, freedom, unity and democracy.